DESEMPEÑO LABORAL EN EL GOBIERNO AUTÓNOMO DESCENTRALIZADO DEL CANTÓN CALUMA - Gaibor Yanez, Lilia Lucia (2019)
The canton Caluma was created on August 23, 1990, by Executive Decree No. 123, reaching at that time to become the sixth Canton of the Province of Bolivar. As can be seen, the Municipal Autonomous Decentralized Government (GADM) of the canton of Caluma is relatively young and therefore still has shortcomings that must be resolved by its authorities, both the Mayor and, of course, the Human Talent Chief of that entity. The regulations that govern the different positions or public positions must be regulated by the functional Organic that has the GADM of Caluma; in which the functions and specifications that have said charges are detailed; that is, what should be done and how should they serve users. In addition all the decentralized autonomous governments are in the Association of Municipalities of Ecuador, among them they offer collaboration to be able to improve their autonomy and the performance of their collaborators; as well as raise levels of efficiency and effectiveness both in collections and in providing better services to citizens